A Bibliometric Study of Sharia Compliance in Islamic Banking - Syihabudin, Syihabudin; Wanto, Deri; Zakaria Syafe’i; Adawiah, Amalia Muazzah; Hadji Latif, Sahraman D. (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the scholarly discourse on Islamic law and its application in Islamic banking using bibliometric analysis and a Systematic Literature Review (SLR). The aim is to obtain an overview of the productivity of academics in the field of Islamic economics and its influence on the development of Islamic banking. This type of research is library research whose primary materials are literature and certain journals, especially the Journal of Islamic Accounting and Business Research. This study reveals a continuous increase in academic interest since 1989, in line with a significant increase in publications since 2007, and peaked in 2020, before finally tending to decline. This study found fluctuating author productivity, with considerable consistency from academics such as Alam MK and Hassan MK. Several key terms, such as maqāshid al-sharīa, murābahah, and ijārah, used in their writings reflect their relevance to Islamic banking practices. Several contemporary studies even offer critical perspectives on the implementation of Islamic law in the banking world and emphasize innovation in Sharia-compliant financial products. This study confirms that Islamic law plays a crucial role in defining the identity and ensuring the legitimacy of Islamic banking institutions.